2016
DOI: 10.1186/s13617-016-0047-0
|View full text |Cite
|
Sign up to set email alerts
|

Automated tracking of lava lake level using thermal images at Kīlauea Volcano, Hawai’i

Abstract: Tracking the level of the lava lake in Halema'uma'u Crater, at the summit of Kīlauea Volcano, Hawai'i, is an essential part of monitoring the ongoing eruption and forecasting potentially hazardous changes in activity. We describe a simple automated image processing routine that analyzes continuously-acquired thermal images of the lava lake and measures lava level. The method uses three image segmentation approaches, based on edge detection, short-term change analysis, and composite temperature thresholding, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In addition, Hawaiian LFs are normally 200-400 m high (Head and Wilson, 1987;Wolfe et al, 1988), whereas on Etna we measured LF up to 3-4 km in height during the lapse of time here considered ( Table 1). It is worth noting that during the explosive activity of Kilauea observed on 17 May 2018, when a summit circular vent was active within the Halemaumau Crater (Patrick et al, 2016), a more than 9 km high ash plume was reported 1 This suggests that, considering all other parameters as steady, a circular vent might promote a greater vertical distribution of the erupted ash when compared to a fissure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Hawaiian LFs are normally 200-400 m high (Head and Wilson, 1987;Wolfe et al, 1988), whereas on Etna we measured LF up to 3-4 km in height during the lapse of time here considered ( Table 1). It is worth noting that during the explosive activity of Kilauea observed on 17 May 2018, when a summit circular vent was active within the Halemaumau Crater (Patrick et al, 2016), a more than 9 km high ash plume was reported 1 This suggests that, considering all other parameters as steady, a circular vent might promote a greater vertical distribution of the erupted ash when compared to a fissure.…”
Section: Discussionmentioning
confidence: 99%
“…Lava level is inferred from thermal images acquired by a stationary camera located on the east rim of Halemaʻumaʻu Crater (Figure ) and calibrated using theodolite, lidar, and laser rangefinder measurements (mostly the latter). Instrumentation and methodology are described in detail by Patrick et al [, , , ]. During 2011–2015, the lava level within Kīlauea's summit eruptive vent fluctuated over a range of more than 200 m (Figure a), although levels were relatively stable for the majority of this time period.…”
Section: Methodsmentioning
confidence: 99%
“…Bebbington [2010] compared trends and clustering of volcanic activity including many references on globally applicable cases. Thus, hazard estimates are often based only on the spatial distributions of specific hazardous actions conditional on the occurrence of a specific or an ensemble of volcanic events [e.g., Todesco et al, 2006;Costa et al, 2009;Neri et al, 2015;Macedonio et al, 2016] and ignore the temporal aspects. Long-term temporal models are therefore necessary to provide a comprehensive assessment of hazard to be used for urban planning and risk reduction of the territory.…”
Section: Introductionmentioning
confidence: 99%